In-Situ Measurement Of Electrode Wear During Edm Drilling Using Vision System - Zamzuri, Hamedon; Razemi, M. N. I.; Azmir, Azhari; A. R., Yusoff (2016)
Machine vision system is an image-based technology use to perform automatic inspection and analysis such as process control and robot guidance. The aim for this project is to develop a fully automated electrode wear detection system in EDM by using machine vision system and apply this system in detecting electrode wear in EDM. This project was conducted using DSLR camera as monitoring device. The electrode undergo hole making process with a depth of 10 mm,20 mm,30 mm,40 mm, and 50 mm to observe the electrode condition. The image of the electrode will be remotely captured from the laptop and then will undergo image processing process using Matlab software to calculate and determine the electrode wear. The output of this project will show the images of the electrode wear and its wear value. Findings from the project show that this system is suitable and applicable in EDM super drill machine to monitor the tool condition.